+0  
 
0
32
1
avatar

The graph of $y = f(x)$ is shown below. 

 

 

For each point (a,b) that is on the graph of y = f(x), the point \(\left( 3a - 1, \frac{b}{2} \right)\) is plotted, forming the graph of another function y = g(x). As an example, the point (0,2) lies on the graph of $y = f(x),$ so the point \((3 \cdot 0 - 1, 2/2) = (-1,1)\) lies on the graph of y = g(x).

 

Express g(x) in terms of f(x).

 Nov 10, 2020
 #1
avatar
-1

By using appropriate transformations, we can show that g(x) = 2*f((x - 3)/3).

 Nov 11, 2020

33 Online Users

avatar
avatar
avatar
avatar
avatar